1992
DOI: 10.1177/106002809202601005
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Suspected Immunologic-Based Hypersensitivity Reactions to Etoposide Therapy

Abstract: Based upon these cases and other literature reports, we believe these reactions primarily represent a type II or immunologic-based hypersensitivity reaction to etoposide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…The etiology and the exact mechanism are unknown, but they are believed to be of nonimmunogenic origin. Nevertheless, there are some hypotheses that the concentration of the drug and the rate of infusion could explain HSR [5]. Another possible way of HSR is that the additive used in the preparation to dissolve etoposide (benzyl alcohol, polysorbate 80) may cause HSR.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology and the exact mechanism are unknown, but they are believed to be of nonimmunogenic origin. Nevertheless, there are some hypotheses that the concentration of the drug and the rate of infusion could explain HSR [5]. Another possible way of HSR is that the additive used in the preparation to dissolve etoposide (benzyl alcohol, polysorbate 80) may cause HSR.…”
Section: Discussionmentioning
confidence: 99%
“…Bernstein and Troner (1999) have attributed etoposide HSRs to the concentration of the drug and the rate of infusion. However, other authors have reported HRSs in patients receiving a wide range of etoposide concentrations, weakening this hypothesis (Kasperek and Black, 1992;Bernstein and Troner, 1999;Athanassiou et al, 1988;De Souza et al, 1994;Tester et al, 1990;Hoetelman et al, 1996;Siderov and Zalcberg, 1994;Tucci and Pirtoli, 1985;Donegan, 1989;Eschalier et al, 1988;Schacter, 1996). Another suggested hypothesis is that the vehicle used to dissolve the etoposide (benzyl alcohol and polysorbate (tween) 80) is responsible for the HSR (Weiss, 1996).…”
Section: Case Descriptionmentioning
confidence: 96%
“…There are no known risk factors for developing a HSR to etoposide, and in few of the reported cases do the patients have a history of drug allergy (Kasperek and Black, 1992;Bernstein and Troner, 1999;Athanassiou et al, 1988;De Souza et al, 1994;Tester et al, 1990;Hoetelman et al, 1996;Siderov and Zalcberg, 1994;Tucci and Pirtoli, 1985;Donegan, 1989;Eschalier et al, 1988;Schacter, 1996).…”
Section: Case Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,4] Another possible route is that the additive used in preparation to dissolve etoposide (benzyl alcohol, polysorbate-80) may cause hypersensitivity reactions. The concentration of the drug and the rate of infusion are both accused, but there are a wide range of etoposide concentrations and rate to cause HSR to etoposide.…”
Section: Etoposide? or Polysorbate-80?mentioning
confidence: 99%